The drivers of social entrepreneurship: agency, context, compassion and opportunism. Issue 6 (2nd February 2021) - Stirzaker, Rebecca; Galloway, Laura; Muhonen, Jatta; Christopoulos, Dimitris
Abstract : Purpose: The paper refers to the drivers of social entrepreneurship and critically explores the notion that it is prompted by a personal mission to enable some social or ideologically motivated altruism. It refers to Shapero's Entrepreneurial Event Theory and the adaptation of it for social entrepreneurship in Mair and Noboa (2006) and develops these so that both agency and context may be considered. Design/methodology/approach: Fieldwork comprised a qualitative sample of 12 life-story narratives of social entrepreneurs in Central Scotland. The location was chosen because of its reputation for support of social entrepreneurship, and the qualitative methodology allowed for a depth of inspection and analysis of complex and situational experiences. Findings: Findings include observation of altruism but there are other drivers, including the appeal of the social entrepreneurship business model. Context emerges as a critical feature of social entrepreneurship too, including spurs for altruism and the human, financial and social capitals, skills and experiences of social entrepreneurs. Originality/value: The paper finds that the social entrepreneurship process involves both agency and context and is complex, and for some, reflects a strategic approach similar to commercial entrepreneurship. The paper also proposes further adaptation to Entrepreneurial Event Theory to capture this complexity of the social entrepreneurship process.